Formulation of Instant Granule of Japanese Taro Tuber Extract (Colocasia esculenta L. Schoot) Based on Milk With Various Binders for Stunting Prevention - Budiati, Anarisa; Kartiningsih; Satrio Damar Wicaksono (Journal of Natural Product for Degenerative Diseases, 2024)
Japanese taro root extract (Colocasia esculenta L. Schoot) includes Fe and Zn, which the body need to prevent stunting. The goal of this investigation was to see how different binder types affected the physical and chemical properties of instant granule preparations. The formula for an instant granule dry extract of Japanese taro root was developed using the wet granulation method with various binders, including PVP (F1), Mucillago amili (FII), and Na-CMC (FIII), and then tested for physical, chemical, and Fe and Zn content using Atomic Absorption Spectrophotometry. The test findings showed that the flow rate of instant granules of Japanese taro root extract formulations I, II, and III was (4.6840-4.7956) g/s, with an angle of repose of 26.86-31.08°. The granules had particle sizes ranging from 670,2295-703,2438 μm, a compressibility index of 15.91-19.00%, and moisture content of 2.80-3.58%. The immediate granule test was performed after being dispersed in water; formulations I, II, and III had dispersion periods of 40.33-50.33 seconds, specific gravity of 1.0099-1.0101 g/mL, viscosity of 1.3589-1.6352 cps, sedimentation volume of 0.940-0.955, and pH of 6.60-6.65. Formulas II using 10% muchilago amyl binder had the greatest Fe and Zn levels, at 34.40 mg/kg and 16.19 mg/kg, respectively. The statistical test revealed a significant effect of different binders on angle of repose, moisture content, dispersion time, pH, and viscosity of Japanese taro root extract granules (p-value < 0.05).